Worrying about work? Disentangling the relationship between economic insecurity and mental health - Paul Fiedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Literature encompassing economic insecurity and its relationship with mental health has increased significantly in recent years. While the association of job insecurity and mental health has been researched extensively, less is known about the general relationship between economic insecurity and mental health. This paper analyses the simultaneous influence of six different economic insecurity indicators on mental health focusing on private sector employees. Using German longitudinal micro-data and applying a fixed effects model, this paper finds a significant negative relationship between a broad range of economic insecurity factors and mental health. Specifically, the relationship stems from self-perceived risks such as economic anxiety and job insecurity as opposed to macroeconomic anxiety or objective factors, such as workforce reductions or substantial income losses. This strongly suggests that subjective measures of economic insecurity matter more for mental health than objective ones. Furthermore, the empirical results are robust with respect to various model specifications. From a policy perspective, this paper calls for improved provision of mental health services and also an increased awareness of mental health problems combined with generally de-tabooing the discussion of mental health.
Keywords: I14; I31; J01; 330; mental health; economic insecurity; fixed effects; private sector employees; SOEP